INCLUSIVE EDUCATION AND MODERN PEDAGOGICAL APPROACHES - Rahimjanova Muqaddas Dilmurod qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation This article explores the essence of inclusive education in modern pedagogy, emphasizing its significance in ensuring equal opportunities for all learners regardless of their physical, social, or cognitive differences. The study also examines recent European research (2023–2025) highlighting innovative teaching methods, teacher training, and policy reforms that promote inclusivity. The analysis concludes that inclusion is not only a social obligation but also a pedagogical strategy for sustainable development in education.